'Creatures of a Day': Contingency, Mortality, and Human Limits. (October 2021) - Carel, Havi
Abstract: This paper offers a nexus of terms – mortality, limits, contingency and vulnerability – painting a picture of human life as marked by limitation and finitude. I suggest that limitations of possibility, capacity, and resource are deep features of human life, but not only restrict it. Limits are also the conditions of possibility for human life and as such have productive, normative, and creative powers that not only delimit life but also scaffold growth and transformation within it. The paper takes a less known interpretation of the term ' ephēmeros ', to mean 'of the day', rather than 'short-lived' and suggests that as ephemeral, human life is contingent and mutable, subject to events beyond our control. However, virtue can still be exercised – indeed, can be exuberantly displayed – when we respond to contingent events marked by adversity.